2017
DOI: 10.1007/s10980-017-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal dynamics of the agricultural landscape mosaic drives distribution and abundance of dominant carabid beetles

Abstract: International audienceContext Agroecosystems are dynamic, with yearly changing proportions of crops. Explicit consideration of this temporal heterogeneity is required to decipher population and community patterns but remains poorly studied. Objectives We evaluated the impact on the activity-density of two dominant carabid species (Poecilus cupreus and Anchomenus dorsalis) of (1) local crop, current year landscape composition, and their interaction, and (2) inter-annual changes in landscape composition due to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…This suggests that such changes must be accompanied by changes at wider scales, notably at the landscape scale or even in a way that contributes to mitigate climate change. These results coincide with studies showing that landscape-level crop diversity enhance pest control (Redlich et al, 2018) and that some specific crop rotations considered at the landscape scale greatly influence carabid distributions within agricultural landscapes (Marrec et al, 2017).…”
Section: Relative Effects Of Environmental Context Vs Resource and Di...supporting
confidence: 89%
“…This suggests that such changes must be accompanied by changes at wider scales, notably at the landscape scale or even in a way that contributes to mitigate climate change. These results coincide with studies showing that landscape-level crop diversity enhance pest control (Redlich et al, 2018) and that some specific crop rotations considered at the landscape scale greatly influence carabid distributions within agricultural landscapes (Marrec et al, 2017).…”
Section: Relative Effects Of Environmental Context Vs Resource and Di...supporting
confidence: 89%
“…Crop habitat filtering was the highest in late spring, while it was almost inexistent in early spring. This seemingly random assembly of species in early spring can be explained by the fact that abundance-activity of carabid species in fields does not entirely depend on the present crop type, but mainly on the previous crop type(s) in the succession, and on the landscape context as carabid may colonize crops from nearby habitats at the onset of the growing season (e.g., Marrec et al, 2015, 2017). Because of crop rotation, farmlands are highly dynamic landscapes, both in space and time.…”
Section: Discussionmentioning
confidence: 99%
“…The study (Pajač Živković et al 2018) showed the positive effect of exclusion nets on A. dorsalis in an apple orchard of Croatia, thus confirming their value in assessing the introduction of new agricultural measures into practice. Marrec et al (2017) evaluated the impact made on activity and density of A. dorsalis by local crops, current year, landscape composition, and their interaction, and inter-annual changes in landscape composition due to crop rotations. Pitfall traps were installed in 188 fields in France, and the results revealed the beetle to be more abundant in oilseed rape and landscapes with a higher proportion of oilseed rape in the previous year.…”
Section: Discussionmentioning
confidence: 99%